Bridging long-term vision and entrepreneurial orientation: The role of learning orientation and willingness to change in family firms - Karamjit Kaur (VERLAG proWiWi e.V., 2025)
Family firms play a crucial role in fostering innovation and ensuring long-term competitiveness; nonetheless, their entrepreneurial behavior varies considerably. Drawing on stewardship theory, this study examines the impact of long-term orientation (LTO) on entrepreneurial orientation (EO) in family firms through two cultural mechanisms: learning orientation (LO) and willingness to change. Using secondary data from 208 German family firms, the analysis was conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4 to test both direct and mediated relationships among LTO, EO, LO, and willingness to change. The results indicate that LTO has no direct effect on EO, and LO does not mediate this relationship. In contrast, willingness to change significantly mediates the relationship between LTO and EO. Among the control variables, firm age and generational involvement show negative associations with EO, whereas CEO tenure has no significant effect. The study advances existing knowledge by clarifying how LTO shapes family firms' EO and by emphasizing adaptability as a behavioral mechanism linking continuity with renewal. Practically, it emphasizes how family firms must foster adaptability in order to maintain continuity while pursuing innovation.
urn:nbn:de:gbv:ilm1-202520045
Keywords: 650; Family Firms; Long-Term Orientation; Entrepreneurial Orientation; Learning Orientation; Willingness to Change; Stewardship Theory